Stacked Microsurgical Autologous Flap Breast Reconstruction Is an Ideal Option after Unilateral Nipple-Sparing Mastectomy - Frey, Jordan D.; Alperovich, Michael; Ahn, Christina Y.; Allen, Robert J. (Journal of Reconstructive Microsurgery Open, 2016)
Background Nipple-sparing mastectomy (NSM) allows for complete preservation of the nipple-areola complex and is increasing in popularity. Autologous options in NSM provide an aesthetic reconstruction in a single stage; however, donor tissue may be scarce in these patients. Stacked microsurgical breast reconstruction, especially in unilateral cases, is an attractive alternative in NSM that is yet to be described.Methods Patients undergoing NSM with stacked autologous flap reconstruction were identified with demographics, intraoperative variables, and outcomes analyzed.Results Six patients who underwent unilateral NSM with stacked autologous free flaps were identified. The average patient age was 50.17 years and body mass index was 21.67. Average follow-up was 28.62 months. Five (83.3%) patients underwent unilateral NSM and reconstruction for a therapeutic indication. The average mastectomy weight was 235.67 grams. All patients were reconstructed with stacked deep inferior epigastric perforator flaps. The average total flap weight was 397.33 grams. Anastomoses in five stacked flaps (83.3%) were performed in an anterograde/retrograde fashion to the internal mammary (IMA) vessels. In one (16.7%) stacked flap, the two flaps were anastomosed in series to the IMA. There were no major complications and three incidences of minor complications. There were no incidences of partial or complete flap loss. The average number of secondary procedures was 0.83 per patient.Conclusion Stacked microsurgical autologous breast flaps provide an optimal reconstruction after NSM and may be considered the reconstruction of choice in patients undergoing unilateral NSM with inadequate donor site tissue for single-flap reconstruction.
Keywords: nipple-sparing mastectomy; autologous reconstruction; breast cancer